Persepsi Nasabah Terhadap Tingkat Kualitas Pelayanan Bank Syariah Cabang Malang - Iffah, Lailatul (FALAH: Jurnal Ekonomi Syariah, 2018)
This study aims to determine the perceptions of customers on the level of service quality of Syariah Mandiri Bank Malang branch based on five dimensions of service quality. This research used quantitative method with research subjects on BSM savings customers who used mudharabah muthlaqah contract of Syariah Mandiri Bank Malang branch. The data used in this study is the primary data through questionnaires. Questionnaires were distributed to customers as much as 53 questionnaires and sampling techniques using Purposive Sampling method. The result of the research showed that customer perception of Syariah Mandiri Bank Malang branch is very satisfied under the perception of emphaty dimension as dimension which dominates customerâs perception toward service quality of the Bank.